APPLICATION OF SAFETY PERFORMANCE BASED ON JOB INVOLVEMENT, PERSONALITY, AND LEARNING ORGANIZATION ON THE CHILD OF PT. ASDP INDONESIA FERRY SURABAYA - Sofyan Sauri; Pompong B. Setiadi; Sri Rahayu (Dinasti Publisher, 2022)
Psychological empowerment is useful in improving performance, individuals become more effective, increasing productivity, motivation to work more. Thus, psychological empowerment provides many benefits to every individual who wants to change his life for the better which of course must be supported by the safety performance, so that there are no obstacles in improving performance and productivity. psychological empowerment can have an influence on individuals, organizations, and society. The results in this studyfound that psychological empowerment dimensions of meaning, self-determination, and impact have an influence on physical and mental health, and have a major influence on job satisfaction. Therefore, to overcome the impact caused by the powerlessness of employees, it is necessary to involve the safety performance in empowering its employees. In the development of Psychological Empowerment there is a gap, namely Psychological Safety is a form of employee behavior consisting of work safety components. Forms of work safety behavior, such as using work safety equipment and actively participating in work safety program activities in the organization. Neal and Griffin also added that the concept of safety performance is employee behavior in the workplace related to organizational safety. Psychological Safety is also defined as a form of employee safety behavior at work which includes compliance and participation. Compliance is defined as employee safety behavior at work and maintaining safety at work, participation is described as employee voluntary behavior to develop the organization's work safety. It can be concluded that Psychological Safety is a form of employee behavior at work which includes the prevention of work accidents by means of employee behavior that complies with established safety rules and procedures and voluntarily participates in improving work safety in the company.